2006
DOI: 10.1007/s10350-006-0570-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Chemotherapy May Not Be Necessary for Patients With ypN0-Category After Neoadjuvant Chemoradiotherapy of Rectal Cancer

Abstract: These retrospective data suggest that, for some patients, postoperative chemotherapy can be spared. For patients with ypN2 status, an intensification of the postoperative chemotherapy should be considered. Further evaluation in prospective studies is urgently recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 35 publications
4
55
0
1
Order By: Relevance
“…Although patients who treated with postoperative chemotherapy had higher 5-year overall survival and disease-free survival rates compared with patients who were not treated postoperatively, the differences between the groups were not statistically significant. These findings are consistent with the suggestion by Das et al [4] that postoperative chemotherapy may be of greater benefit for high-risk patients, and the recommendation by Fietkau et al [5], who reported that postoperative chemotherapy may be unnecessary in patients with ypN0. However, the results are contrary to those of Janjan et al [6], who found a significant improvement in cancer-specific survival in response to neoadjuvant chemoradiotherapy and the administration of postoperative chemotherapy.…”
Section: To the Editorsupporting
confidence: 90%
“…Although patients who treated with postoperative chemotherapy had higher 5-year overall survival and disease-free survival rates compared with patients who were not treated postoperatively, the differences between the groups were not statistically significant. These findings are consistent with the suggestion by Das et al [4] that postoperative chemotherapy may be of greater benefit for high-risk patients, and the recommendation by Fietkau et al [5], who reported that postoperative chemotherapy may be unnecessary in patients with ypN0. However, the results are contrary to those of Janjan et al [6], who found a significant improvement in cancer-specific survival in response to neoadjuvant chemoradiotherapy and the administration of postoperative chemotherapy.…”
Section: To the Editorsupporting
confidence: 90%
“…As a result, it appears logical to treat these patients aggressively with adjuvant chemotherapy [55,59,6365] . Unfortunately, Breugom et al [36] in the metaanalysis of five trials (described above) showed no benefit of adjuvant chemotherapy neither in stage Ⅱnor in stage Ⅲ, however there was no data available for stage 0 and Ⅰ disease.…”
Section: Milinis K Et Al Adjuvant Chemotherapy In Rectal Cancermentioning
confidence: 99%
“…112,113 The need for adjuvant CT in patients with a complete or near-complete response after CRT has been questioned. 114,115 Recent work from a multi-institutional retrospective analysis of 3,133 patients shows that the benefit of adjuvant therapy differs between LARC subgroups. For example, patients with ypT1-2 or ypT3-4 tumors benefitted the most from adjuvant therapy compared with patients who had ypT0N0 tumors.…”
mentioning
confidence: 99%